PENDEKATAN PRAGMATIK CERPEN HANA KARYA AKUTAGAWA RYUUNOSUKE TERHADAP PEMBACA - Megasar, Victoria Eny (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2013)
Hana is a short story that tells about a chief priest at Ike no O temple named Zenchi Naigu. Naigu had a long nose like a sausage, people around the temple were talking about Naigu’s nose everyday, he depressed because of that situation. Naigu tried to find a way to shorten his nose. He found the way from a Chinese physicians, a person that he knew in Kyouto. In short, Naigu’s nose can be shorten like normal people in general, but people around the temple even laugh at him because of his nose. Finally, Naigu regreted his New nose and in his remorse, Naigu’s nose suddenly return to the normal length. Since then, Naigu felt relieve and comfortable with the shape of his long nose.The purpose of this study is to find out what and how themes, characters and characterizations, plot, and setting in ‘Hana’ short story. Based on the analysis above the writer tried to understand the moral of the story from the Hana short story to be used as a lesson for the reader after reading this short story. Keywords : Hana, Akutagawa, Pragmatic